2019
DOI: 10.1136/bmjstel-2019-000470
|View full text |Cite
|
Sign up to set email alerts
|

Managing psychological safety in debriefings: a dynamic balancing act

Abstract: Debriefings should promote reflection and help learners make sense of events. Threats to psychological safety can undermine reflective learning conversations and may inhibit transfer of key lessons from simulated cases to the general patient care context. Therefore, effective debriefings require high degrees of psychological safety—the perception that it is safe to take interpersonal risks and that one will not be embarrassed, rejected or otherwise punished for speaking their mind, not knowing or asking questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 65 publications
8
151
0
5
Order By: Relevance
“…Our findings overall reinforce previous research across the fields of higher education, health professions education and communication, which have reported that learning behaviours are fostered by trust, respect, empathy, seeking to understand the learners’ perspective and an attitude that accepts mistakes as inevitable during learning 29,32,50 . In simulation‐based education, a set of ‘promising practices’ have been proposed for creating a safe context for learning, derived from a literature review and the team's expertise 39,40 . These included clarifying expectations; attending to logistical details; showing respect and curiosity regarding participants’ perspectives; understanding that mistakes occur in challenging learning environments, focusing on assisting learners to enhance their skills and maintaining positive regard for them.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings overall reinforce previous research across the fields of higher education, health professions education and communication, which have reported that learning behaviours are fostered by trust, respect, empathy, seeking to understand the learners’ perspective and an attitude that accepts mistakes as inevitable during learning 29,32,50 . In simulation‐based education, a set of ‘promising practices’ have been proposed for creating a safe context for learning, derived from a literature review and the team's expertise 39,40 . These included clarifying expectations; attending to logistical details; showing respect and curiosity regarding participants’ perspectives; understanding that mistakes occur in challenging learning environments, focusing on assisting learners to enhance their skills and maintaining positive regard for them.…”
Section: Discussionsupporting
confidence: 83%
“…This is important for learning outcomes as excessive anxiety distracts attention, interferes with complex thinking and impairs memory 7‐34,59 . This theme aligns closely with guidelines for simulation‐based education and doctor‐patient communication skills, which outline the importance of setting the tone for a collaborative partnership from the start 35‐58 …”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Elective simulation opportunities were recognized as unique spaces where students can learn terminology with more opportunity than workplace settings to clarify ambiguous or novel terms, and with less perceived identity and social risk. Other studies have also commented on the ability of simulation to provide a psychologically safe learning environment [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%